Polymodal activation of the TREK-2 K2P channel produces structurally distinct open states. - McClenaghan, C; Schewe, M; Aryal, P; Carpenter, E; Baukrowitz, T; Tucker, S (Rockefeller University Press, 2016)
The TREK subfamily of two-pore domain (K2P) K+ channels exhibit polymodal gating by a wide range of physical and chemical stimuli. Crystal structures now exist for these channels in two main states referred to as the “up” and “down” conformations. However, recent studies have resulted in contradictory and mutually exclusive conclusions about the functional (i.e., conductive) status of these two conformations. To address this problem, we have used the state-dependent TREK-2 inhibitor norfluoxetine that can only bind to the down state, thereby allowing us to distinguish between these two conformations when activated by different stimuli. Our results reconcile these previously contradictory gating models by demonstrating that activation by pressure, temperature, voltage, and pH produce more than one structurally distinct open state and reveal that channel activation does not simply involve switching between the up and down conformations. These results also highlight the diversity of structural mechanisms that K2P channels use to integrate polymodal gating signals.